Utilisation de paramètres bioécologiques pour analyser la biodiversité ichtyologique de l’Aire Marine Protégée (AMP) de Joal-Fadiouthau Sénégal et sa périphérie non protégée à la pêche - Sarr, Serigne Modou; Thiaw, Modou; Mbengue, Balla Aramane (European Scientific Journal, ESJ, 2018)
With global changes, concerns about marine ecosystems and population dynamics are of increasing interest to researchers. As such, knowledge of the specific biodiversity of exploited marine ecosystems is generally considered a key factor in their resilience. This paper is a comparative study that focuses on analyzing the bioecological effects of MPA Joal-Fadiouth on fish populations by comparing the inside vs. outside of the MPA. Data were collected from scientific surveys conducted in cold and hot seasons in 2015. In each survey, 16 stations were sampled; 9 inside the MPA and 7 outside. The MPA is in open Ocean and the analysis of environmental parameters shows that the MPA area is a homogeneous environment. The variability is at the seasonal level. This variability is similar inside and outside the MPA. A total of 67 species in 37 families were found in the reserve, against 41 species in 32 families outside MPA. The biological indicators analysis shows a similar species richness and biomass between the two areas. However, total abundance is higher in the protected area. On the other hand, larger fish are more likely to be outside the protected area. In the MPA, 20 species sampled are in spawning period, but over 80 % of individuals are immature. The Joal-Fadiouth MPA implementation significantly improves the conservation of biodiversity with a dominance of herbivorous species and lower trophic levels. In addition, the reserve is a nursery area for many species (sardines, octopus, and shrimp) and reproduction for some species characteristics of the area, e.g.Hemiramphus brasiliensis and Stephanolepis hispidus.